THE ROLE OF IMMUNOLOGICAL RESEARCH IN THE HEALTHCARE SYSTEM OF UZBEKISTAN (Modern American Journal of Medical and Health Sciences, 2025)
Modern medicine is increasingly paying attention to the human immune system, as it plays a key role in maintaining health and protecting the body from infectious, autoimmune, tumor, and allergic diseases. Immunological studies allow us to identify primary and secondary immunodeficiency states, allergic, autoimmune and inflammatory processes.